REQUIREMENTS FOR DIDACTIC SOFTWARE AIMED AT PRIMARY SCHOOL (Journal of Information Technologies in Education (ITE), 2012)
This article has an overview of the traditional requirements for didactic software, analyzed age and individual characteristics of younger pupils and defined additional requirements – the need to rely on a visual representation of information, carry out practical actions with objects, to ensure a balance between the playful and didactic content, account the experience of pupils and their individual capabilities, to have tools for situation of success.
Keywords: didactic software; elementary school; the requirements